Tratamiento de Agua Residual de Beneficio de Conejos (2020)
This paper shows the conceptual design of three alternatives for the treatment of wastewater from the rabbit slaughter process of a company located in the municipality of El Rosal (Cundinamarca), in accord with the physicochemical and microbiological characterization of wastewater. The alternative selected consist of grease trap, upflow anaerobic filter and chlorination to allow the reuse of treated water in crop irrigation. The alternative meets the removal efficiency required by the standard and the cost-benefit requirements.